User-focused, User-led: Space Assessment to Transform a Small Academic Library - Hillman, Christina; Blackburn, Kourtney; Shamp, Kaitlyn; Nunez, Chenisvel (Evidence Based Library and Information Practice, 2017)
Objective – By collecting and analyzing evidence from three data points, researchers sought to understand how library spaces are used. Researchers have used results for evidence based decision making regarding physical library spaces.Methods – Undergraduate researchers, sociology faculty, and librarians used mixed-methods to triangulate findings. Seating sweeps were used to map patrons’ activities in the library. Student-led focus groups discussed patterns of library use, impressions of facilities, and library features and services. The final step included a campus survey developed from seating sweeps and focus group findings.Results – Seating sweeps showed consistent use of the library's main level Learning Commons and upper level quiet spaces; the library’s multipurpose lower level is under-utilized. Students use the main level of the library for collaborative learning, socializing, reading, and computer use. Students use the upper level for quiet study and group work in study rooms. Focus group findings found library use is task-specific. For example, a student may work with classmates on a project using the main level Learning Commons during the day, and then come back at night to use the quiet floor for test preparation. Survey responses highlighted areas in which the library is deficient. For example, respondents cited crowdedness, noise levels, and temperature concerns.Conclusion – These data offer empirical evidence for library space needs. Some data aligns with previous space studies conducted at this library: access to power outlets, lighting, noise, and an outdated environment. Evidence also supports anecdotal concerns of crowding, graduate students lacking designated study space, and the need for quiet study space away from group study space.